Exploration of self-identification through the mask form and world culture - Hadfield, Michael (My University, 2011)
Mask-making is much more than merely a devoted pastime of ancient cultures and elementary school projects. It is the intention of this research paper to explore the historical background of various cultural masks and their purpose and process. Through this cultural investigation, I will also delve into the connection between mask making and expressing one's self identity. This includes a cohesive body of work through studio exploration and investigating the meaning behind mask-making itself.
Plan B Paper. 2011. Master of Science in Education-Fine Arts--University of Wisconsin-River Falls. Art Department. 88 leaves. Includes bibliographical references (leaves 38-39).
Keywords: Art--Study and teaching; Mask form; Masks; Self identity; Mask making